National and European strategies and policies for the generation change in Romanian agriculture - Geanina-Valentina Lupu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The aging of the population is a real phenomenon and even more so highlighted in the agricultural field. The statistics highlight the fact that there are about 10% more elderly Romanian farmers than the European average. The causes of this fact lie in the aging population, the departure of young people abroad, difficulties in attracting young people to agricultural education. The need for technologicalization in agriculture also requires young entrepreneurs who are able to learn and apply such innovative technologies. The measures provided by European funds to attract young farmers are proving insufficient to ensure the renewal of generations in agriculture and to achieve sustainable development. Governments are trying to apply strategies and policies, some implemented according to the requirements of the European Union, which aim to attract the NEET category in the agricultural sector, coherent measures in the high school, vocational and dual education system to attract young people to vocational training with agriculture and entrepreneurship. The paper analyzes quantitatively and qualitatively statistical data on enrollment figures, accessing non-reimbursable funding provided by the National Rural Development Program to young farmers, various measures under the Common Agricultural Policy, other legislative initiatives. There is a better correlation of the educational offer for all levels with the real requirements of the agricultural field and the adoption of concrete measures to facilitate the transition from subsistence to efficient and attractive agriculture for young generations, allowing a renewal in this sector so important for the Romanian economy.
Keywords: I25; J58; 330; farmer; young; agricultural education; financing; NRDP